2021
DOI: 10.3390/molecules26195823
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Chemical–Physical Characterization, and Biomedical Applications of Functional Gold Nanoparticles: A Review

Abstract: Relevant properties of gold nanoparticles, such as stability and biocompatibility, together with their peculiar optical and electronic behavior, make them excellent candidates for medical and biological applications. This review describes the different approaches to the synthesis, surface modification, and characterization of gold nanoparticles (AuNPs) related to increasing their stability and available features useful for employment as drug delivery systems or in hyperthermia and photothermal therapy. The syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 288 publications
(327 reference statements)
1
57
0
Order By: Relevance
“…Nano-spray drying plants are not designed for the production of nanopowders in large quantities. Powders obtained in this way can be used where reproducible morphology and purity of the product are necessary, for example, in the synthesis of drug carriers [ 120 , 121 ].…”
Section: Nanoscale Delivery Systemsmentioning
confidence: 99%
“…Nano-spray drying plants are not designed for the production of nanopowders in large quantities. Powders obtained in this way can be used where reproducible morphology and purity of the product are necessary, for example, in the synthesis of drug carriers [ 120 , 121 ].…”
Section: Nanoscale Delivery Systemsmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] In recent years, several approaches to metal and metal oxide NP fabrication and application have been developed to impart functionalities to different types of textile substrates [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, nanomaterials, such as gold and silver nanoparticles, stabilized by opportune functional capping agents, have been used as a novel class of functionalizing nanofillers either themselves [ 24 , 25 , 26 , 27 , 28 , 29 ] or for the functionalization of different types of materials (such as concrete, glass, geopolymer and also embedded in coloring or antibacterial coatings), especially for textile fabrics [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The second stage is nucleation, in which the metal atoms in the solution continue to collide with one another, clustering to form nuclei. The final stage is growth, in which more solids are gradually deposited on the surface of the nucleus until the nucleus grows to a critical size, thereby forming a nanoparticle [ 5 , 18 , 19 , 20 ]. However, most of the chemicals employed in metallic nanoparticle preparation are toxic, and improper treatment of these chemicals could lead to environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the preparation of environmentally friendly, low-temperature-sintering metallic nanoparticles has become a research trend [ 21 , 22 , 23 , 24 ]. In past research [ 18 , 25 , 26 ], reports clearly demonstrated that ascorbic acid is a popular reducing agent. It is a natural and mild reducing agent with antioxidant properties and is widely used as a food preservative.…”
Section: Introductionmentioning
confidence: 99%